Role of empowerment and identification with work teams in innovation climate - Montoya Ramírez, Manuel Fernando (2020)
Several studies argue that an organizational climate oriented to promote innovation generates greater competitiveness in companies. However, very few researchers have explored the factors that lead to the formation of innovation climate and their effects on workers’ performance. Based on a sample of 201 workers from manufacturing and service companies, an analysis was carried out to examine the influence of variables like empowerment and Identification with work teams in innovation climate. Furthermore, the influence of innovation climate on job performance and work commitment was analyzed. The results indicate that there is a positive relationship among the variables of the hypotheses, empowerment and Identification with work teams influence in innovation climate, and the latter influences work performance and work commitment.